PERSEPSI DAN KESIAPAN GURU PAI TERHADAP ASESMEN AUTENTIK BERBASIS PROYEK PADA KURIKULUM MERDEKA: ANALISIS DESKRIPTIF DI SMA NEGERI 2 KABUPATEN BUNGO - Pahmi Idris; Andryadi; Yulia Friska, Sonia; Baili; sabli, Muhammad; kurniawan, sugeng (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
The Merdeka Curriculum shifts the assessment paradigm from conventional summative tests to project-based authentic assessment oriented toward developing the Pancasila Student Profile. Islamic Religious Education (PAI) teachers play a crucial role in operationalizing this shift, yet the gap between policy and classroom practice indicates barriers in understanding, designing, and implementing authentic assessment. This study aims to map PAI teachers' perceptions and readiness regarding project-based authentic assessment under the Merdeka Curriculum. The research employed a descriptive quantitative design with qualitative triangulation. Subjects included all PAI teachers at SMA Negeri 2 Regency Y (N=12) selected via census. Instruments consisted of perception and readiness questionnaires (1–5 Likert scale, α=0.91) and semi-structured interview guides. Quantitative data were analyzed descriptively (mean, standard deviation, frequency distribution), while qualitative data underwent thematic analysis for contextual deepening. Results indicate that teachers' perceptions of project-based authentic assessment fall into the positive category (M=3.84; SD=0.52), with strong conceptual understanding but concerns regarding feasibility. Overall readiness is moderate (M=3.61; SD=0.63), with significant disparities in technical-pedagogical dimensions (rubric design, process tracking, digital documentation) and administrative aspects (workload, report card alignment). Qualitative findings reveal four main challenges: lack of contextual PAI operational guidelines, limited time for teacher collaboration, misalignment in reporting systems, and the need for sustained mentoring. The study concludes that PAI teachers cognitively and affectively accept authentic assessment, but implementation readiness remains constrained by technical, systemic, and school capacity factors. Recommendations include developing standardized PAI assessment modules, strengthening Professional Learning Communities (PLCs), simplifying administration, and implementing continuous mentoring programs. The results provide empirical input for policy development on PAI teachers' assessment competencies in the Merdeka Curriculum era.